2020
DOI: 10.1016/j.kint.2020.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin 1 channels in renin-expressing cells influence renin secretion and blood pressure homeostasis

Abstract: Kidney function and blood pressure homeostasis are regulated by purinergic signaling mechanisms. These autocrine/paracrine signaling pathways are initiated by the release of cellular ATP, which influences kidney hemodynamics and steady-state renin secretion from juxtaglomerular cells. However, the mechanism responsible for ATP release that supports tonic inputs to juxtaglomerular cells and regulates renin secretion remains unclear. Pannexin 1 (Panx1) channels localize to both afferent arterioles and juxtaglome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 79 publications
2
18
0
Order By: Relevance
“…Moreover, not only cell–cell communication via gap junctions seems to be important for the regulation of renin secretion but also signaling via connexin hemichannels [ 36 ]. A recent study suggests that pannexin 1 could also be involved in the regulation of basal renin secretion through mediating intercellular communication [ 14 ]. Another cell adhesion molecule essential for mediating cell–cell or cell–matrix interactions is β1-integrin, which is abundantly expressed in the kidneys including renin-lineage cells.…”
Section: Identity Of Renin-expressing Cellsmentioning
confidence: 99%
“…Moreover, not only cell–cell communication via gap junctions seems to be important for the regulation of renin secretion but also signaling via connexin hemichannels [ 36 ]. A recent study suggests that pannexin 1 could also be involved in the regulation of basal renin secretion through mediating intercellular communication [ 14 ]. Another cell adhesion molecule essential for mediating cell–cell or cell–matrix interactions is β1-integrin, which is abundantly expressed in the kidneys including renin-lineage cells.…”
Section: Identity Of Renin-expressing Cellsmentioning
confidence: 99%
“…As a control to rule out ATP secretion by connexins, we found that the Cx43 peptide inhibitor Gap19 did not affect EFS-induced constriction (Figure 4D-F and Supplemental Figure 6). Genetic Panx1 deletion has been used to demonstrate an important role in blood pressure regulation by renin-secreting cells 18 (where genetic deletion causes hypertension) and by SMC 3 (where genetic deletion causes hypotension). Because iSMC Panx1 OE mice displayed increased EFS induced vasoconstriction we hypothesized these mice would have elevated blood pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of work has focused on Panx1 as an ATP channel, with multiple stimuli inducing ATP secretion as a paracrine signaling pathway. However, physiologic roles for Panx1 are not limited to secretion, as more recent evidence has shown that Panx1 can also act as a plasma membrane calcium channel, increasing cytosolic calcium in response to stimuli, such as TNFα [ 29 , 30 ]. Several other solutes have been shown to be transmitted through Panx1 including fluorescent tracers, anandamide, lactate, glutamate, spermidine, and bacterial products, consistent with roles for Panx1 in multiple different signaling pathways [ 26 , 27 , 31 33 ].…”
Section: Pannexin 1 Structure Function and Post-translational Modificationsmentioning
confidence: 99%
“…This is in comparison to constitutive phosphorylation of Y198 on the intracellular loop of Panx1 which was found to be important for Panx1 channel opening. A mimetic peptide against this region (“PxIL2P”) was able to inhibit Panx1 current, ATP release, and alpha-adrenergic vasoconstriction; more general Panx1 inhibition was also noted in endothelium and renin-secreting cells [ 5 7 , 30 , 49 , 59 ]. Although the Y308 site has not been found to be as important in terms of plasma membrane localization or trafficking, it is similar to Y198, in that it was important for gating properties, including ATP release and current [ 10 , 60 ].…”
Section: Pannexin 1 Structure Function and Post-translational Modificationsmentioning
confidence: 99%
See 1 more Smart Citation